Kataklizmične spremenljive zvezde - Skok, Krištof (Matrika, 2019)
Cataclysmic variables are an example of short period binary stars. First the geometry of the system is discussed along with its time evolution which is determined by the mass transfer between the stars. Then follows the explanation of the non-conservative evolution where the system's angular momentum is lost by radiation of gravitational waves and magnetic braking. Later is an overview of accretion disks and the last two chapters focuse on two phenomena connected to cataclysmic variables - classical novea where the luminosity of the system is abruptly increased because of thermonuclear explosion of hydrogen layer on the white dwarf; and dwarf novea where the luminosity of the accretion disk periodically varies due to its varying structure and temperature.
Keywords: astronomija; astronomy; spremenljivke; stars; variable stars; zvezde